Reshaping the world: debates on Mesoamerican cosmologies - Díaz, Ana, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
An exploration of the plurality, complexity, and adaptability of Precolumbian and colonial-era Mesoamerican cosmological models and the ways anthropologists and historians have used colonial and indigenous texts to understand these models. That model comprised nine fixed layers of underworld and thirteen fixed layers of heavens.--Provided by publisher.
Introduction: rethinking the Mesoamerican cosmos / Ana Díaz -- Colliding universes: a reconsideration of the structure of the pre-Columbian Mesoamerican cosmos / Jesper Nielsen and Toke Sellner Reunert -- Incorporating Mesoamerican cosmology within a global history of religion: some considerations on the work of Lorenzo Pignoria / Sergio Botta -- Dissecting the sky: discursive translations in Mexican colonial cosmographies / Ana Díaz -- The colonial encounter: transformations of indigenous Yucatec conceptions of k'uh / Gabrielle Vail -- Zapotec travels in time and space: the correlation between the 260-day cycle and a multi-level cosmological model / David Tavárez -- A cosmology of water: the universe according to the Ch'orti' Maya / Kerry Hull -- Distance and power in classic Maya texts / Alexandre Tokovinine -- The sky, the night and the number nine: considerations on the Nahua vision of the universe / Katarzyna Miku'lska -- Creating and destroying the upper part of the cosmos: a new approach to Wixarka cosmology / Johannes Neurath.
Keywords: Indian cosmology; Indians of Mexico -- Religion; Indians of Central America -- Religion; Indians of Mexico -- Rites and ceremonies; Indians of Central America -- Rites and ceremonies